Statement on bioinformatics and capturing the benefits of genome sequencing for society - Benjamin Capps; Ruth Chadwick; Yann Joly; Tamra Lysaght; Catherine Mills; John J. Mulvihill; Hub Zwart (Human Genomics, 2019)
Abstract The HUGO Committee on Ethics, Law and Society (CELS) undertook a Working Group exploration of the key ethical issues arising from genome sequencing in 2013. The Imagined Futures paper the group subsequently published proposed points to consider when applying genomic bioinformatics to data repositories used in genomic medicine and research (http://www.hugo-international.org/Resources/Documents/CELS_Article-ImaginedFutures_2014.pdf). Given the ever-increasing power to sequence the human genome rapidly and inexpensively—as well as trends toward “Big Data” and “Open Science”—we take this opportunity to update and refine the key findings of that paper.